Drug-Eluting Bead Bronchial Arterial Chemoembolization With and Without Microwave Ablation for the Treatment of Advanced and Standard Treatment-Refractory/Ineligible Non-Small Cell Lung Cancer: A Comparative Study - Xu, Sheng; Bie, Zhi-Xin; Li, Yuan-Ming; Li, Bin; Kong, Fan-Lei; Peng, Jin-Zhao; Li, Xiao-Guang (Frontiers in Oncology, 2022)
Purpose To compare the outcomes of drug-eluting bead bronchial arterial chemoembolization (DEB-BACE) with and without microwave ablation (MWA) for the treatment of advanced and standard treatment-refractory/ineligible non-small cell lung cancer (ASTRI-NSCLC). Materials and Methods A total of 77 ASTRI-NSCLC patients who received DEB-BACE combined with MWA (group A; n = 28) or DEB-BACE alone (group B; n = 49) were included. Clinical outcomes were compared between groups A and B. Kaplan–Meier methods were used to compare the median progression-free survival (PFS) or overall survival (OS) between the two groups. Univariate and multivariate Cox proportional hazards analyses were used to investigate the predictors of OS for ASTRI-NSCLC treated with DEB-BACE. Results No severe adverse event was found in both groups. Pneumothorax was the predominant MWA-related complication in group A, with an incidence rate of 32.1% (9/28). Meanwhile, no significant difference was found in DEB-BACE-related complications between groups A and B. The overall disease control rate (DCR) was 61.0% (47/77), with a significantly higher DCR in group A (85.7% vs. 46.9%, P = 0.002). The median PFS in groups A and B was 7.0 and 4.0 months, respectively, with a significant difference (P = 0.037). The median OS in groups A and B was both 8.0 months, with no significant difference (P = 0.318). The 6-month PFS and OS rates in groups A and B were 75.0% and 78.6%, 22.4% and 59.2%, respectively, while the 12-month PFS and OS rates in groups A and B were 17.9% and 28.6%, 14.3% and 22.4%, respectively. Of these, a significantly higher 6-month PFS rate was found in group A (75.0% vs. 22.4%; P < 0.001). The cycles of DEB-BACE/bronchial artery infusion chemotherapy [hazard ratio (HR): 0.363; 95% confidence interval (CI): 0.202–0.655; P = 0.001] and postoperative immunotherapy (HR: 0.219; 95% CI: 0.085–0.561; P = 0.002) were identified as the predictors of OS in ASTRI-NSCLC treated with DEB-BACE. Conclusion MWA sequentially combined with DEB-BACE was superior to DEB-BACE alone in the local control of ASTRI-NSCLC. Although the combination therapy reveals a trend of prolonging the OS, long-term prognosis warrants an investigation with a longer follow-up.